2017
DOI: 10.3892/ijmm.2017.3099
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and synergism of ursolic acid 3-O-α-L-arabinopyranoside with oxacillin against methicillin-resistant Staphylococcus aureus

Abstract: The objective of the present study was to investigate the antibacterial activity of a single constituent, ursolic acid 3-O-α-L-arabinopyranoside (URS), isolated from the leaves of Acanthopanax henryi (Oliv.) Harms, alone and in combination with oxacillin (OXA) against methicillin-resistant Staphylococcus aureus (MRSA). A broth microdilution assay was used to determine the minimal inhibitory concentration (MIC). The synergistic effects of URS and OXA were determined using a checkerboard dilution test and time-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…Another factor that argues against cross-transmission is the large number of different strains discovered ( 28 ). The effect of specific antibiotics on MRSA strains has been previously analysed ( 29 ). It was shown that the resistance level of MRSA in patients who received antibiotic therapy was 2-fold compared to that in those who did not undergo antibiotic treatment ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that argues against cross-transmission is the large number of different strains discovered ( 28 ). The effect of specific antibiotics on MRSA strains has been previously analysed ( 29 ). It was shown that the resistance level of MRSA in patients who received antibiotic therapy was 2-fold compared to that in those who did not undergo antibiotic treatment ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…ursolic acid (1) and oleanolic acid (2) have already exhibited antimicrobial properties and its mechanism is established. 21,22 Oleanolic acid has also exhibited anti-tubercular activity. 23 The derivatives of oleanolic acid have been reported for the treatment of pancreatic cancer, 24 and oleanolic acid saponins have shown significant antimicrobial properties, 25 and the combination of oleanolic acid with hypocrellin A has been reported for the treatment of hepatocellular carcinoma diseases, 26 and oleanolic acid derivative SZC014 has exhibited anticancer activity.…”
Section: Resultsmentioning
confidence: 99%
“…ursolic acid (1) and oleanolic acid (2) have already exhibited antimicrobial properties and its mechanism is established. 21,22 Oleanolic acid has also exhibited anti-tubercular activity. 23 The derivatives of oleanolic acid have been reported for the treatment of pancreatic cancer, 24 and oleanolic acid saponins have shown significant antimicrobial properties, 25 and the combination of oleanolic acid with hypocrellin A has been reported for the treatment of hepatocellular carcinoma diseases, 26 and oleanolic acid derivative SZC014 has exhibited anticancer activity.…”
Section: Resultsmentioning
confidence: 99%